2010
DOI: 10.1007/s10096-010-0873-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pneumococcal vaccines on invasive pneumococcal disease in Taiwan

Abstract: In Taiwan, the 23-valent pneumococcal polysaccharide vaccine (PPV23) and the 7-valent pneumococcal conjugate vaccine (PCV7) have been available since January 2001 and October 2005, respectively. A hospital-based surveillance of invasive pneumococcal disease (IPD) in a medical center was conducted from 2000 to 2008 to evaluate the epidemiologic changes after pneumococcal vaccination. A total of 337 episodes in 328 patients were identified. The cumulative coverage rate of PPV23 among persons of age >or=75 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 7 publications
0
25
0
Order By: Relevance
“…The lack of data on adult pneumococcal disease and the doubts regarding the effectiveness of vaccination, particularly in immunocompromised patients, may be factors in the limited use of the pneumococcal vaccination [36]. However, several recent studies have shown decreases in economic burden of pneumococcal disease after the introduction of vaccinations [37,38].…”
Section: Discussionmentioning
confidence: 97%
“…The lack of data on adult pneumococcal disease and the doubts regarding the effectiveness of vaccination, particularly in immunocompromised patients, may be factors in the limited use of the pneumococcal vaccination [36]. However, several recent studies have shown decreases in economic burden of pneumococcal disease after the introduction of vaccinations [37,38].…”
Section: Discussionmentioning
confidence: 97%
“…Following the introduction of pneumococcal vaccines, a decline in the incidence of pneumococcal infections was documented [15,25]. Furthermore, our study showed that currently available pneumococcal vaccines would provide optimal efficacy both against HA-IPD and CA-IPD in Taiwan because >70% of the pneumococcal isolates from both groups were those included in the pneumococcal vaccines.…”
Section: Discussionmentioning
confidence: 90%
“…Clinical diagnoses associated with IPD were classified as invasive pneumococcal pneumonia, meningitis, primary bacteraemia and other syndromes, as described in a previous report [15]. Pneumococcal meningitis was defined as the isolation of pneumococcus from CSF, or the clinical diagnosis of meningitis and isolation of pneumococcus from any sterile site.…”
Section: Definitionsmentioning
confidence: 99%
“…69 The highest mortality rate (over 50%) of IPD was seen in older adults. 70 However, national recommendations for PPV23 use in the elderly population are controversial and are based primarily on a risk-based strategy, which likely partially explains the low vaccine coverage rates in Europe. 71 Moreover, the production of specific antibodies after vaccination decreases progressively in the extremely elderly population.…”
Section: Pneumococcal Vaccinationmentioning
confidence: 99%